v.3 - All India Congress Committee (New Delhi, 1985)
The third volume of the Centenary History deals with the manner in which the Congress, under the stewardship of Mahatma Gandhi, Jawaharlal Nehru and a distinguished galaxy of nationalist leaders, finally liberated India from the shackles of British imperialism.
Keywords: Political Parties-India